Webinar Digital Marketing Dan Pendampingan Digital Marketing Melalui Sosial Media Untuk UMKM - Djoko Wijono (Pusat Riset dan Inovasi Nasional, 2022)
During the Covid-19 pandemic, many MSMEs are having difficulty marketing their businesses. So digital marketing is the right solution to help business marketing by utilizing digital technology. This marketing can be done through social media such as Instagram by creating interesting content. The objects of this service are 33 MSME actors. The aim of this community service is to provide education to MSMEs, especially business actors, about digital marketing strategies and provide training via webinars on how to optimize business accounts via social media. The service method is carried out in a bold way through training webinars and mentoring using the zoom meeting application. As a result of the service activities, participants were able to understand good marketing strategies using digital marketing.